129 Balancing patient benefit and risk of resistance: An audit of hospice antimicrobial prescribing. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Cannon, Jasmine; McConnell, Robert; Brown, Jolene; Hughes, Andrew
Abstract : Background: Antimicrobial stewardship aims to improve the safety and quality of patient care and reduce the risk of antimicrobial resistance. Symptoms of infection are often part of the natural deterioration towards end of life. Clinical evidence for the benefit of antimicrobials at the end-of-life is scarce and results inconclusive. Within our hospice, our aim of prescribing effectively whilst observing the principles of advance care planning led to an audit of practice as part of our antimicrobial stewardship. Methods: A retrospective audit was completed of all patients admitted over 3 months, where antimicrobials had been prescribed, considering; whether antimicrobials were prescribed in accordance with local trust guidelines; presence of indication, review and stop dates on each prescription and whether advance discussions were documented in relation to the use of antimicrobials. Results: Of 56 admissions identified, 23 (41%) patients had 37 individual antimicrobials prescribed. The commonest sources of infection were chest (18), urinary tract (4), skin and soft tissue (4). Adherence to local trust guidance was evident with regards choice of antimicrobial in 59%. The indication was recorded on the drug chart in 100%, with a review date in 35% and a stop date in 86%. Advance discussions relating to antimicrobial treatment were documented in 48%. Seventeen patients died during the admission; the average time between stopping antimicrobials and death was 8 days. Conclusions: This audit highlights the importance of accessing updated guidelines which ensure appropriate prescribing whilst considering local resistance patterns. Alongside a drive to raise awareness, an advance care planning template was implemented for all patients, to record discussions and guide decision making when indications of infection arise. The continuing challenge lies in identifying patients who will benefit from the right antimicrobial and those for whom there will be minimal benefit, but could contribute to increasing antimicrobial resistance.